EVALUASI PENGELOLAAN UNIT PRODUKSI DI SMK NEGERI 1 MANDAU - Lydia Oktaviany; Azhar Azhar; Sudirman AS (Universitas Riau, 2019)
The purpose of this research is to know and analyze the implementation of program management unit production in SMK Negeri 1 Mandau in terms of context, input, process and product activity. This study used a qualitative approach with the type of case study research. Based on the aspects evaluated in this research, the evaluation model of Context (C), Input (I), Process (P), and Product (P) or CIPP is used. The subjects in this study are the principal, head of production units and students who follow the activities of the production unit. Data collecting techniques in this study are interviews, observation, documentation and questionnaires. Data analysis is done through data collection, data reduction, data presentation and verification and conclusion. The results of processing and data analysis show that (1) The implementation of the context component has not been done well, because the environmental conditions are less supportive. (2) Implementation of the input component has been running well enough, planning and organizing of resources has been done in accordance with organizational management prerequisites. (3) The implementation of process components has been running well enough, the implementation and supervision of activities are in accordance with the planning. (4) The implementation of product components has been running well, production unit activities have been able to create students who have entrepreneurial spirit, have skill and competitive and master technology in line with national education objectives.